A gold nanoparticle-modified indium tin oxide microelectrode for in-channel amperometric detection in dual-channel microchip electrophoresis. Issue 29 (13th July 2017) - Zhu, Gangzhi; Song, Qianhui; Liu, Wenfang; Yan, Xingxing; Xiao, Jian; Chen, Chuanpin
Abstract : A modified indium tin oxide (ITO) microelectrode detector integrated with a dual-channel polydimethylsiloxane (PDMS) microchip is proposed for in-channel amperometric detection in microchip electrophoresis (ME). Abstract : A modified indium tin oxide (ITO) microelectrode detector integrated with a dual-channel polydimethylsiloxane (PDMS) microchip is proposed for in-channel amperometric detection in microchip electrophoresis (ME). The gold nanoparticle (GNP)-modified ITO-coated poly-ethylene terephthalate film electrode was fabricated via a photolithography process and direct electrochemical deposition. This electrode fabrication method reduced the cost of this microchip a lot. The electroplating conditions for the GNP-modified ITO electrode were optimized through evaluating the effect on the detection sensitivity and separation efficiency of a dual-channel ME system. Under the optimal conditions, the performance of the new ME amperometric detection system has been demonstrated by analyzing a mixture of p -aminophenol, o -aminophenol and m -aminophenol, which achieved the detection limits of 0.24 μM, 0.41 μM and 0.42 μM, respectively. Finally, the successful detection of antibiotics demonstrated the potential of this dual-channel microchip system for clinical application.